How Amazon trees growth are affected and react to forest fragmentation and climate changes? A dendrochronology approach - Albiero Junior, Alci (2019)
Trees are considered key elements of tropical forests, playing central roles in maintaining and balancing of the ecosystems with which they are associated and in providing environmental services that are indispensable for human well-being. Because they are sessile and long-lived beings, they become excellent temporal bioindicators of past and present environmental changes to which they are exposed throughout their lives. Currently, the conservation of the world\'s largest rainforest is strongly threatened by advances in deforestation rates and the Antropocene climate changes. In this context, through a dendrochronological perspective, the present study aimed to evaluate how trees occupying different vertical profiles of the terra firme forest in central Brazilian Amazonia are affected by edge effects and climate change and react to these phenomena during their lifetime. Through tree rings we reveal that Scleronema micranthum (Ducke) Ducke (Malvaceae) trees located in the forest canopy are more sensitive to edge effects and climate change, showing an 18% reduction in their growth rates during the first 10 years of forest fragmentation. Opposite results to those observed for Theobroma sylvestre Mart. (Malvaceae) trees located under forest canopy that increased their growth rates by approximately 6% during the first 20 years of fragmentation. Confirming that structural and climate changes caused by edge effects and large-scale climate changes mainly related to oceans warming and cooling exert contrasting differences in tree growth dynamics depending on their position in the vertical profile of the forest. Therefore, we highlight the relevance of tree rings as bioindicators of forest fragmentation and local and large-scale climate change to which trees are exposed during their lives. Providing new perspectives on Amazonian trees resilience, corroborating with forest management and restoration practices in future scenarios of fragmentation and global warming.